Can thoughts be read from the brain? Neuroscience Contra Wittgenstein. - Wenzel, Christian Helmut (Synthese, 2022)
Wittgenstein wrote: “No supposition seems to me more natural than that there is no process in the brain correlated with associating or with thinking; so that it would be impossible to read off thought-processes from brain processes.” In general, he rejects what he calls “psycho-physical parallelism.” In Sect. 1, I explain Wittgenstein’s position on this topic and how his followers defend it. In Sect. 2, I argue against Wittgenstein, contending that there is “thought” in a wider sense and that it can be “manifested” without expression. Thought does not need to be ordinarily expressed or even expressible, and it can be read off from the brain, provided one has sufficient technology, data, and understanding of the subject’s interaction with the environment. In Sect. 3, I offer results from brain-science in support of my claims.